Analisis Kinerja Petugas Terminal Service Officer (TSO) Terhadap Pengawasan Fasilitas Pt Angkasa Pura I Bandar Udara Internasional El Tari Kupang - Gustania Dora Pereira Soares De Jesus; Septiyani Putri Astutik (CV. Aksara Global Akademia, 2023)
The Terminal Service Officer, or better known as the Terminal Inspection Service, is a work unit tasked with supervising all facilities in the Land Side area of the airport, curb/sidewalk, parking area and terminal building. Before the airport operates, the Terminal Service Officer ensures or checks in advance whether all facilities are ready to operate or not, if one of these facilities is not ready, it will affect the operational processes of El Tari Kupang International Airport and can also pose a risk to the performance of TSO officers. . The purpose of this research is to find out the performance and efforts of Terminal Service Officers in resolving obstacles to facility monitoring at El Tari Kupang International Airport. This study used a qualitative descriptive method using data from interviews with 3 Terminal Service Officers, observation and documentation. The data analysis technique used in this study is data reduction, data presentation and drawing conclusions. Based on the results of this study, Terminal Service Officers (TSO) have duties and responsibilities that are in accordance with Standard Operating Procedures including facilities that are the responsibility of Terminal Service Officers, especially the land side area, passenger terminal and departure/arrival area, carry out routine checks supporting facilities to keep them operating properly. If in carrying out the supervision there is a damaged facility, it will be immediately coordinated with the unit concerned and repaired immediately.